Konseling Sebaya untuk Menurunkan Kecenderungan Prokrastinasi Akademik pada Siswa - Denta, Mirnani (Cognicia, 2019)
Academic procrastination can be stated as a procrastination tendency to start up or finish an academic assignment; thus, if the behavior is allowed, it will give bad impacts to the students. Therefore, it is needed a way that can be used to decrease the academic procrastination of the Senior High School (SMA) students, in which it is by using the peer counseling. This research aimed at discovering the effectiveness of peer counseling to decrease the academic procrastination tendency on the 11th grade students of Senior High School (SMA). This research was a quasi-experimental research using the pre-test post-test control group design. The research subjects were determined by using the purposive sampling, in which there were 20 students that consisted of 10 students of experimental group and 10 students of control group. The data collection method used the Tuckman Procrastination Scale (TPS) which analyzed by using the Wilcoxon analysis test and the Mann Whitney test. The research results showed that there was a difference on the score of academic procrastination (Z = -3,445; ρ = 0,001<0,05). Therefore, it can be concluded that the peer counseling can be used to decrease the academic procrastination tendency on the 11th grade students of Senior High School (SMA).